Evolving Trends of Chinese Folk Music and Performing Arts Management in the Digital Age: A Bibliometric Analysis of Scopus-Indexed Articles Published between 2013 and 2024 - Sayam Chuangprakhon; Qianqian Liu; You Lin; Warakorn Seeyo; Shujia Dong (Institut Seni Indonesia Yogyakarta, 2025)
This bibliometric analysis outlines relevant studies concerning Chinese folk music and performing arts management in the digital era, grounded in English-language publications indexed in the Scopus database between 2013 and 2024. This period was selected because English-language articles regarding digital approaches to Chinese folk music began to appear consistently during this time and reached a sufficient volume for a systematic bibliometric analysis. This analysis aims to provide insights into the intellectual landscape, the development of various themes, and the digital impact on the management of culture, artistic management, and the preservation of culture. Under the PRISMA protocol, 39 research articles were examined in the Scopus peer-reviewed database. The dataset was limited to English-language journal articles and conference papers that did not include publications from Chinese-language databases, which define the scopes and boundaries of the analysis. Each of the outputs was analyzed using bibliometric mapping, and quantitative publication trends and patterns concerning institutions and authors were complemented with qualitative thematic analysis, resulting in five thematic clusters. There is a noticeable increase in research results after 2020, aligning with digital cultural policy development in China and the growing use of online platforms for cultural dissemination. Given the relatively small dataset of 39 publications, findings should be interpreted as a focused analytical snapshot rather than a comprehensive representation of all articles on Chinese folk music. The results indicate a shift from ethnographic preservation toward the integration of digital technology to enhance audience engagement, interdisciplinary collaboration, and educational practice. The study underlines how digital integration reshapes the management of Chinese folk music by positioning technology as a tool for both cultural preservation and a medium of creative expression.